Exploring the effect of sedentary behavior on increased adiposity in middle-aged adults - Nayeli Macías; Eric Monterrubio-Flores; Jorge Salmerón; Joacim Meneses-León; Yvonne N. Flores; Alejandra Jáuregui; Deborah Salvo; Umberto Villa; Armando G. Olvera; Katia Gallegos-Carrillo (BMC, 2024)
Abstract Background Sedentary behavior is linked to excess fat mass; however, this association may be inconclusive due to potential measurement errors in self-reported sedentary behavior. Objective To assess the association between changes in sedentary behavior and fat mass in a Cohort of Health Workers (HWCS) from 2004 to 2010. Methods A total of 1,285 adults participating in the Cohort of Health Workers were evaluated in 2004 and 2010. Fat mass (kg) was measured by dual X-ray absorptiometry. A self-administered questionnaire was used to estimate the sedentary behavior. Sedentary behavior was also estimated using accelerometry in a sample of 142 health workers. Accelerometry data were used to correct self-reported sedentary behavior using a generalized linear model, which included values for sleeping time, age, sex, sedentary behavior, glucose, and triglycerides. Concordance between both methods was assessed using a kappa and Bland-Altman analysis. Once sedentary behavior was corrected, the values were used to evaluate the association between changes in sedentary behavior and body fat mass using a fixed effect model in the cohort, adjusting for confounders. Results Self-reported sedentary behavior was 2.8 ± 1.8 and 2.3 ± 1.6 h/day, and body fat mass was 24.9 ± 8.1 and 26.8 ± 8.5 kg in 2004 and 2010, respectively. After applying the correction model, the self-reported sedentary behavior was 7.6 ± 1.2 and 7.5 ± 1.2 h/day in 2004 and 2010, respectively. For every hour increase in corrected sedentary behavior, there was an observed increase of 0.847 (p > 0.001) kg in body fat mass during the 6.8 years in the Cohort of Health Workers from 2004 to 2010. Conversely, non-corrected self-reported sedentary behavior was associated with a non-significant reduction of 0.097 kg (p = 0.228) for every hour of sedentary behavior. Conclusions Increased sedentary behavior was associated with increased body fat mass when corrected self-reported sedentary behavior was used. Implementing public health strategies to reduce sedentary behavior is imperative.